2016
DOI: 10.1002/jmv.24607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of influenza A and human respiratory syncytial virus among patients with influenza like illness

Abstract: Influenza A and Respiratory Syncytial Virus (RSV) has been recognized as a major cause of acute respiratory tract infection. H1N1 is one of the subtypes of influenza A, pandemic worldwide in July 2009, causing 18,449 deaths globally. To investigate the prevalence and clinical manifestation of the influenza A, H1N1pdm09, and RSV. Throat/nasal swab collected from the patients of all age group either outpatients/inpatients having respiratory illness from 2 to 5 days. The clinical data were recorded in a predesign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…Our findings overall showed that cough is the most common clinical finding, accounting for approximately 85% of cases whereas fever and nasal congestion were present in >80% and >50% of cases, respectively. These features are consistent with the World Health Organization's (WHO) definition of ILI and previous observations . Symptoms of influenza typically subside within 5‐8 days with 95% of cases in this study reporting a duration of illness of less than a week.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings overall showed that cough is the most common clinical finding, accounting for approximately 85% of cases whereas fever and nasal congestion were present in >80% and >50% of cases, respectively. These features are consistent with the World Health Organization's (WHO) definition of ILI and previous observations . Symptoms of influenza typically subside within 5‐8 days with 95% of cases in this study reporting a duration of illness of less than a week.…”
Section: Discussionsupporting
confidence: 91%
“…IAV is a major cause of epidemics and pandemics in humans, occasioning high morbidity and mortality worldwide (Saxena et al, 2017 ). The IAV infections are widely associated with secondary invasive aspergillosis, even among immunocompetent hosts, including those without classic risk factors (Kwon et al, 2013 ; Alshabani et al, 2015 ; Crum-Cianflone, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory infections (ARI) represent a major threat to public health. Influenza virus (FLUV) and human respiratory syncytial virus (HRSV) respiratory infections are responsible for significant morbidity and mortality in both pediatric and adult population worldwide [1,2]. Seasonal FLUV has been estimated to affect 5-10% of the world's population [3] and by the age of two, practically all children are estimated to have been infected at least once with HRSV [4].…”
Section: Introductionmentioning
confidence: 99%